Healthcare ethics and artificial intelligence: a UK doctor survey - Søren Holm; Daniel Joseph Warrington (BMJ Open)
Objectives To survey UK doctors on their uses of artificial intelligence (AI) and of their views on the ethics and regulation of AI in healthcare.Design Anonymous cross-sectional e-survey.Setting An online survey of UK General Medical Council (GMC) registered doctors.Participants 272 individuals.Main outcome measures Likert-scale responses to questions covering personal use of AI, concerns about AI, requirements for introduction of AI and views on necessary AI regulation in healthcare.Results Most doctors rated themselves as slightly or moderately knowledgeable about AI, with men rating their knowledge levels higher than women. Doctors in training are more likely to have used AI than doctors after training. 37% of doctors who use AI reported using AI to help write the required reflective pieces for their portfolio. Doctors reported concerns about AI regarding patient safety and patients' right to confidentiality. They also expressed a strong desire for further regulation of AI in healthcare and, specifically, for their professional bodies to draft guidelines for the use of AI by doctors.Conclusions This study provides useful insights into UK doctors’ uses of AI in healthcare and their opinions on its introduction and regulation. It provides a case for guidance on the use of AI in the reflective practices of doctors and for further evaluation of doctors’ concerns about AI in healthcare. We call on doctors’ professional bodies (GMC, BMA and royal colleges) to draft professional guidance for doctors using AI.